Sex-Related Differences in Neurosensory Alterations Following Blunt Head Injury - Lumba-Brown, Angela; Niknam, Kian; Cornwell, Jordan; Meyer, Courtney; Ghajar, Jamshid (Frontiers in Neurology, 2020)
Background: There is heterogeneity in neurosensory alterations following mild traumatic brain injury. Commonly assessed neurosensory symptoms following head injury include symptom reports and measures of oculomotor impairment, auditory changes, and vestibular impairment. Hypothesis/Purpose: Neurosensory alterations are prevalent acutely following mild traumatic brain injury secondary to blunt head trauma during collegiate varsity sports and may vary by sex and sport. Study Design: Retrospective study of a large collegiate athletic database. Methods: Analyses were performed using an established single University dataset of 177 male and female collegiate varsity athletes who were diagnosed with concussion/mild traumatic brain injury between September 2013 and October 2019. Descriptive and comparative analyses were performed on individual and grouped acute concussion assessments pertaining to neurosensory alterations obtained within 72 h of injury using components of the Sports Concussion Assessment Tool Version 5 and Vestibular/Ocular-Motor Screening. Results: Females had significantly more abnormal smooth pursuit (p-value: 0.045), convergence (p-value: 0.031), and visual motion sensitivity tests results (p-value: 0.023) than males. There were no differences in neurosensory alterations when grouped by overall auditory, vestibular, or oculomotor impairments. The majority of sports-related concussions occurred during football (50, 28.25%), wrestling (21, 11.86%), water polo (15, 8.47%), and basketball (14, 7.91%). Abnormal vestibular assessments were high in these top four sports categories, but statistically significant differences in overall auditory, vestibular, or oculomotor impairments were not reached by individual sport. However, water polo players had higher abnormal individual assessments related to balance reports on the sideline (60.00%, p-value: 0.045) and in the clinic setting (57.14%, p-value: 0.038) as compared to all other sports. Conclusion: While neurosensory alterations are prevalent in both male and female athletes acutely post-concussion, females have a higher incidence of abnormalities in smooth pursuit, convergence, and visual motion sensitivity and may benefit from early rehabilitation.